2017
DOI: 10.14214/sf.1717
|View full text |Cite
|
Sign up to set email alerts
|

Forwarder crane’s boom tip control system and beginner-level operators

Abstract: Highlights• Boom tip control (BTC) allows the operator to control boom tip movements directly, instead of controlling each movement separately to achieve the desired boom tip movement.• BTC eased boom control, so beginner-level operators using BTC achieved higher productivity than beginner-level operators using a conventional (reference) system. • There were no significant differences in the slopes of learning curves between the systems. AbstractThe forwarder loads processed wood and transports it to a landing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Through automation of work processes interlinked with digitalization [47,48], further research should aim to explore the suitability of technical devices such as rotating cabins or automated crane control to reduce the loading cycle time or the ergonomic strain on the operator. Results from other studies showed that, for example, boom tip control can improve crane work and loading productivity [49,50], in particular since the telescope no longer needs to be operated separately anymore [51][52][53].…”
Section: Influence Of Loading Distance On Time Consumptionmentioning
confidence: 99%
“…Through automation of work processes interlinked with digitalization [47,48], further research should aim to explore the suitability of technical devices such as rotating cabins or automated crane control to reduce the loading cycle time or the ergonomic strain on the operator. Results from other studies showed that, for example, boom tip control can improve crane work and loading productivity [49,50], in particular since the telescope no longer needs to be operated separately anymore [51][52][53].…”
Section: Influence Of Loading Distance On Time Consumptionmentioning
confidence: 99%
“…Another example of the software aiding machine control is the new John Deere 'Intelligent Boom Control' system that allows the operator to control the movement of the head directly, as opposed to moving each individual component of the boom. It has already been shown that the use of such technology makes it easier to learn to operate harvester or forwarder machines and to achieve sustained productivity within a shorter learning time [24,25]. Komatsu recently published a vision of using drones, including communication technologies and cloud services to improve harvesting efficiency.…”
Section: Increased Mechanizationmentioning
confidence: 99%
“…Semi-automation of forestry machines has been success-fully explored before, increasing productivity and reducing the immediate workload on the operator [6,20]. In contrast to methods previously adopted in forestry automation research, the RL framework has shown potential for intelligent and independent end-to-end learning of complex tasks in simulated environments, completely removing the need for analytic low-level controllers.…”
Section: Introductionmentioning
confidence: 99%